The “Oxen of the Sun” hypertext: A digital hypertext in the study of polyphonic translations of James Joyce's Ulysses - Niskanen Lauri A. (Routledge, 2025)
This chapter explores the Oxen of the Sun hypertext (OSH), a digital hypertext created for the analysis of the Finnish and Swedish translations of stylistic imitation, or pastiche, in the “Oxen of the Sun” episode of James Joyce’s Ulysses (1922). The device was created for a doctoral dissertation, A Hubbub of Phenomenon: The Finnish and Swedish Polyphonic Translations of James Joyce’s “Ulysses” (2021), which focused on three episodes of Ulysses and its (re)translations. In the chosen episodes, the intertextuality and intermediality of the text is made explicit through the literary techniques of pastiche, parody, and the musicalisation of fiction. The hypertext and its signal-based method work as analytic aids for the study of how the hypertext of the “Oxen of the Sun” episode refers to its hypotexts from the history of English prose, and how these imitations are re-created in the four Finnish and Swedish translations. In addition to the hypotexts imitated, the “embryonic development” of English prose style, the site offers passages of the Finnish and Swedish target texts and back-translations into English. As imitation is not quotation, analysis of pastiche cannot be based on lexical units. Instead, the OSH method is based on Margaret A. Rose’s “signals of parody”, a method of identifying different “tags”, including syntactic and lexical traits, that operate as triggers for intertextual reading. These can then be compared to the target texts and their respective hypotexts in the target language(s). This chapter discusses the research questions that can be addressed with the hypertext and the methodology the OSH can offer, and it tests the hypertext with two example analyses from the “Oxen” episode, illustrating which types of textual relations can be detected by the digital OSH method.
Using Technologies for Creative-Text Translation